NORMS OF LITERATURE AND SPEECH CULTURE ("Conference on Universal Science Research 2023", 2023)
The study of literary norms in order to determine the boundaries and means of cultural speech with a specific aim is known as speech culture. As a result, the area of speech culture assesses and supervises literary language as well as its normative framework. The literary norm, linguistic norm, linguistic standard, or language norm is a historically defined collection of regularly used language assets, as well as criteria for their selection and usage, that society has recognised as the most suitable in a certain historical period.In this regard, the speech norm may be characterised as a type of self-control exercised by the speaker that corresponds with his perception of the expectations of the other members of the group about the idiosyncrasies of his speech. "Speech culture" is a distinct area of linguistic knowledge, a scientific discipline with definite components, subunits, and rules devoted to that branch of linguistics.